Thinking About the Future: Job Opportunities - Hmong Translation - (:unkn) unknown (My University, 1995)
This curriculum booklet was developed for Milwaukee Public Schools by the Employment and Training Institute. Mao Vang, a UWM student, translated the guide into Hmong for use by families and students at Milwaukee Public Schools. The booklet was designed to help students and their parents use local labor market information and resources in their career planning. The economy is constantly changing because of new technology, shifting consumer demands, international developments and changing demographic trends. A "snapshot" of the labor market, based on local job openings surveys of thousands of Milwaukee area employers, is presented to help students "learn how to keep learning" about their community. Students are encouraged to think about "making" as well as "taking" jobs and work to develop career pathways that offer expanding opportunities for challenging jobs throughout their lifetimes.
Keywords: curriculum; school to work; education for employment